2020
DOI: 10.5114/hm.2020.93425
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and risk factors of sport injuries among amateur football players in Kano, Nigeria

Abstract: Purpose. the purpose of the study was to evaluate football injuries and associated factors in male amateur football players in Kano, North West Nigeria. Methods. A descriptive, cross-sectional survey was conducted among 118 registered male amateur football players aged 16-30 years. the participants were recruited from 7 local football clubs in Kano city. A modified post-season injury questionnaire was used to collect data on football injuries and associated factors. Descriptive and inferential statistics were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Olahraga sepak bola merupakan cara yang efektif untuk meningkatkan tingkat aktivitas fisik dan kebugaran (Hägglund et al, 2013). Pentingnya olahraga ini di negara berkembang tidak dapat dilebih-lebihkan karena memiliki potensi untuk berkontribusi pada pengembangan pribadi dan sosial (Bello et al, 2020).…”
Section: Pendahuluanunclassified
“…Olahraga sepak bola merupakan cara yang efektif untuk meningkatkan tingkat aktivitas fisik dan kebugaran (Hägglund et al, 2013). Pentingnya olahraga ini di negara berkembang tidak dapat dilebih-lebihkan karena memiliki potensi untuk berkontribusi pada pengembangan pribadi dan sosial (Bello et al, 2020).…”
Section: Pendahuluanunclassified
“…players who do high intensity like this, the potential for injury. Frequent and repeated injuries at a young age will have a significant impact on the game in the future [2][3][4][5]. Epidemiological studies report that in several cases it was found that the severity and frequency of injuries on the field in young football players was more visible than in other sports.…”
Section: Introductionmentioning
confidence: 99%
“…Sports injuries are the result of a combination of multiple factors. However, due to the limitations of conventional statistical methods and modelling strategies, previous studies have only been able to obtain only information reflecting some factors in the injury risk pattern but not the complete picture of the injury risk pattern ( Waterkamp et al, 2016 ; Bello et al, 2020 ; Isern-Kebschull et al, 2020 ). Therefore, this study proposes an injury risk multimodal fusion model with generality, interpretability and ease of implementation based on a multimodal fusion strategy to suit the multi-source, multimodal data processing and analysis needs in training monitoring.…”
Section: Introductionmentioning
confidence: 99%